Approximate controllability of fractional control systems with time delay using the sequence method - Xiuwen Li (Electronic Journal of Differential Equations, 2017)
The aim of this article is to establish sufficient conditions for the approximate controllability of fractional control systems with time delay in Hilbert spaces. By the technique of sequential approach, we prove that the fractional control systems with time delay are approximately controllable. Finally, an example is provided to illustrate our main results.